Literary genres and the ethnography of the speech - López García, Ángel (Tropelías: Review of Literary Theory and Comparative Literature, 2019)
This article deals with literary genres from an ethnolinguistic point of view. Current approaches to this topic usually consider literary genres as modalities of literature in where specifical attitudes of the participants are implied: thus, poetry is supposed to emphasize the contribution of the speaker, drama to be directed to the hearer, and narrative to refere on the external world . According to our common assumption such three modalities would characterize western literary tradition, while more "primitive" ones had only developed poetry, or even drama (as it is the case with Chinese and Japanese drama), but never narrative, the most difficult and latest one. By examining three popular genres of ritual discourse in kuna society (a chibcha people from Panamá) this contribution shows that they correlate with the above mentioned types, since literary genres are in relationship to human expressive necessities. The more "primitive" a society looks like, the more "magic" these modalities appear, but their communicative necessity always remains.